Hutchinson Pocket Dictionary of Maths - Publishing, Helicon (Helicon Publishing, 2005)
Reliable information to help you solve mathematical problems.
Keywords: Electronic books. -- local; Mathematics -- Dictionaries; Mathematics -- Philosophy